Czym jest „Zachód” ? - Wandas, Paulina (Investigationes Linguisticae, 2008)
The prevailing majority of words demonstrate high level of uniformity due to their meaning and are related to things existing in reality. However, there is no doubt that lexicology knows words and wording that are highly ambiguous, elusive and there is a huge problem making out some kind of universal definition, acceptable for everyone. The West is one of them. The main aim of the article What is the West ? was to present the range of definitional conceptions and to indicate an extraordinary capacity of meanings to this notion. The article does not deliver the synonymous, ready – made answer to the question of the title but set the readers thinking and make them come to personal conclusions.